Analysis of Influencer's Imitation Behavior Phenomenon, Fear of Missing Out About the Impact on Purchase Intention on Local Cosmetic Products Endorsed by Social Media Influencers - Ika Rahmawati; Rosdiana Sijabat (Budapest International Research and Critics University, 2022)
This study intends to analyze the Influencer Imitation Behaviour and Fear of Missing Out about the impact on Purchase Intention on local cosmetic products which is endorsed by social media influencers. This study is a multivariate causality study. The researcher took the female population in Jakarta, namely quoting from Co-founder of Local Cosmetic Brand SYCA. The number of samples obtained were 200 respondents by the use of purposive sampling because all participating respondents had to meet the specified criteria. The data collected by questionnaires which taken using an online questionnaire method. The analysis using the PLS Structural Equation Modeling (SEM). The findings reveal that Influencer credibility has a positive effect on Influencer imitation behavior, Influencer credibility has a positive effect on fear of missing out the trend (FOMO) behavior, the imitation behavior of influencers has a positive effect on consumers' purchase intentions, and the phenomenon of fear of missing out has a positive effect on consumer purchase intentions.